Modular assembly of self-healing flexible thermoelectric devices with integrated cooling and heating capabilities - Xiaolong Sun; Yue Hou; Zheng Zhu; Bo Zhu; Qianfeng Ding; Wenjie Zhou; Sijia Yan; Zhanglong Xia; Yong Liu; Youmin Hou; Yuan Yu; Ziyu Wang (Nature Communications)
Abstract Flexible thermoelectric devices enable direct energy conversion between heat and electrical energy, making them ideal for wearable electronics and personal thermal management. Yet, current devices lack functional module expansion, which limits the customization for diverse energy-harvesting heat sources and complicates their assembly to meet the specific power requirements of electrical appliances. Moreover, existing devices cannot be stacked to enhance thermoelectric cooling performance while maintaining flexibility and self-healing capabilities. Here, by selectively encapsulating liquid metal electrodes with carbon nanotube-doped self-healing materials with increased thermal conductivity, we substantially improve heat transfer across thermoelectric legs, thereby maximizing energy conversion efficiency. The device achieves a normalized power density of 3.14 μW⋅cm−2 ⋅ K−2, setting a benchmark for self-healing thermoelectric devices. Benefiting from self-healing materials and liquid metal, the device demonstrates both self-healing capabilities and modular assembly, greatly expanding the application scenarios of flexible thermoelectric devices in wearable power generation and refrigeration.